Help‐seeking experiences of men diagnosed with colorectal cancer: a qualitative study. (17th December 2014) - Oberoi, D.V.; Jiwa, M.; McManus, A.; Hodder, R.; de Nooijer, J.
Abstract : Advanced‐stage diagnosis of colorectal cancer (CRC) leads to poor prognosis and reduced survival rates. The current study seeks to explore the reasons for diagnostic delays in a sample of Australian men with CRC. Semi‐structured interviews were conducted in a purposive sample of 20 male CRC patients. Data collection ceased when no new data emerged. Interviews were audiotaped, transcribed and thematically analysed using Andersen's Model of Total Patient Delay as the theoretical framework. Most participants (18/20) had experienced lower bowel symptoms prior to diagnosis. Patient‐related delays were more common than delays attributable to the health‐care system. Data regarding patient delays fit within the first four stages of Andersen's model. The barriers to seeking timely medical advice were mainly attributed to misinterpretation of symptoms, fear of cancer diagnosis, reticence to discuss the symptoms or consulting a general practitioner. Treatment delays were a minor cause for delayed diagnosis. Delay in referral and scheduling for colonoscopy were among the system‐delay factors. In many instances, delays resulted from men's failure to attribute their symptoms to cancer and, subsequently, delay in diagnosis.